Qurra' and Mufassirun opinions on the Wuquf al-Ta'anuq in the holy Quran and its indication on the meaning: A fundamental inductive study / Abdulelah Mohammed Nasser Hazea - Abdulelah Mohammed , Nasser Hazea (2018)
This study investigates opinions of the qurra and mufassirun about how two cases of waqf intersect in the Qur’an. The purpose of this study is to discuss the concept, types and criteria of waqf. The study demonstrates the importance and benefits of waqf in accordance with Sunnah and Qur’an. The study demonstrates the different opinions and consensuses of Muslim scholars concerning al-Waqf and al-Ibtidaa. The study also discusses and demonstrates the different perspectives that Muslim scholars have adopted in respect to what is more accurate and reliable concerning the controversial issues of waqf and al-Ibtidā’. The researcher first discussed the places where two waqf intersect in the Qur’an, and second manifested, classified the origin of the first studies of waqf, and third stated the different perspectives and opinions of Muslim scholars about waqf in different versions of the Qur’an. Besides that the researcher demonstrated the different opinions and perspectives that show the most accurate opinions and consensus concerning waqf. The researcher conducted this study by searching, reading, meditation and looking at the different books of waqf, exegeses of the Qur’an, qirrat and language. Furthermore, the researcher looked at the different opinions of famous acknowledged Muslim scholars who chose their accurate interpretations and perspectives in accordance with the knowledge that they got from its core origin. Furthermore, the study aims to extract new cases of waqf. The researcher has discovered new types of waqf that had not been discovered before by scholars, fifty-nine Waqf, although all these cases of waqf fulfill the conditions of waqf. The researcher first found that some cases of waqf are clearer and more accurate than others and second some cases of waqf should be avoided in some versions of the Qur’an. This may be due to the ambiguity surrounded such cases. The researcher experimentally VI studied every case of waqf in order to first take all misunderstandings and lack of consensus away, and second to thoroughly classify all cases of waqf in respect to which Muslim scholars’ opinions are more accurate and agreed on than others. The researcher discussed different scholars’ opinions in order to distinguish between these opinions. The researcher considered the analysis of opinions and sayings about waqf in order to differentiate between the types of waqf. The researcher used both the inductive and analytical approaches depending on the experimental case study having been used in order to connect the scientific side of the study to the experimental one. This makes the study clearer and more realistic. The researcher classified and clarified this comparison in tables in order to clarify, classify and make the comparison easier. The researcher concluded first that some of the books of the exegeses of the Qur’an are full of valuable knowledge about waqf. These books mention issues of waqf, that the majority of readers are not aware of , either explicitly or implicitly. Despite that these books have not discussed all cases of waqf ( which are about intersecting two cases of waqf). The researcher investigated the issues of waqf that had not been investigated and studied before, and there is still much for other researchers to investigate about waqf. This is because the Qur’an is holy ,whose wonders and miracles are countless. The researcher recommends for other specialized researchers to look for, meditate and investigate other special types of waqf, because there is still a room for other studies and other opinions are still permissible and the blessings of Allah are still given. It is possible that recent studies about waqf are more accurate and comprehensive about waqf. Thus, this may enrich educational institutes, enlighten students and guide other researchers to look for more cases of waqf, particularly, where two cases intersect in the Qur’an.